Gut dysbiosis in primary sarcopenia: potential mechanisms and implications for novel microbiome-based therapeutic strategies - Yang, Wei; Si, Si-Cong; Wang, Wei-Hua; Li, Jing; Ma, Yi-Xin; Zhao, Huan; Liu, Jia (Frontiers in Microbiology, 2025)
Primary sarcopenia is characterized by a progressive loss of skeletal muscle mass, strength, and physical function that occurs with aging. Despite the related adverse or even serious health outcomes, no medications are currently available for treating primary sarcopenia. Here, we discuss recent advancements in understanding the mechanistic role of gut microbiota-muscle cross-talk in primary sarcopenia, and the therapeutic implications. The mechanistic insights encompass a causal role of gut dysbiosis in primary sarcopenia, potentially mediated through gut microbiota-derived bioactive metabolites, such as short-chain fatty acids (SCFAs), secondary bile acids, and their associated signaling pathways, which may be translated into the development of new microbiome-based treatment and diagnostic approaches. Furthermore, we identify challenges that need addressing in future studies to facilitate the translation into potential novel treatment and differential diagnosis for older individuals with sarcopenia.